Sulfonated Diels-Alder Poly(phenylene) Membrane for Efficient Ion-Selective Transport in Aqueous Metalorganic and Organic Redox Flow Batteries. Issue 3 (10th March 2023) - Robb, Brian H.; George, Thomas Y.; Davis, Casey M.; Tang, Zhijiang; Fujimoto, Cy H.; Aziz, Michael J.; Marshak, Michael P.
Abstract : Redox flow batteries (RFBs) can achieve long lifetimes and high performance when employing highly selective and conductive membranes. Neutral and alkaline RFBs suffer from higher resistances due to lower cation conductivity, compared to acidic RFBs utilizing proton transport. We report the use of a sulfonated Diels-Alder poly(phenylene) membrane that exhibits low and stable potassium area specific resistance and high efficiency RFB cycling relative to Nafion, as well as undetectable ferricyanide crossover. An alkaline (pH 12) organic anthraquinone derivative RFB using this membrane demonstrates over 10 days of cycling without capacity loss from crossover. A neutral chelated chromium complex RFB using this membrane demonstrates a peak discharge power of 1.23 W cm −2, and 80% energy efficiency (EE) cycling at an average discharge power density of 446.3 mW cm −2 . Finally, the membrane exhibits similar favorable conductivity for many monovalent cations, opening the opportunity to improve the cycling and crossover performance of other acidic, neutral, and alkaline RFBs.